2010
DOI: 10.1021/la100558x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assembly and Electropolymerization of 3,4-Ethylenedioxythiophene on Au(111) Single Crystal Electrode as Probed by In Situ Electrochemical STM in 0.10 M HClO4

Abstract: We have used electrochemical scanning tunneling microscopy (EC-STM) to obtain molecular insights on the adlayer structures and electrochemical polymerization of 3,4-ethylenedioxythiophene (EDOT) on a bare Au(111) single crystal electrode in 0.1 M HClO(4) solution. Cyclic voltammetric (CV) studies showed an increase in anodic current at 0.90 V with the oxidation of EDOT monomer occurring at E = 1.10 V (vs reversible hydrogen electrode). In situ STM revealed, for the first time, that EDOT molecules can spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In comparison, for monomer modified Au(1 1 1) electrodes, the characteristic peaks of Au(1 1 1) disappear and double layer charging zone prevails from 0 to 0.9 V. This indicates that admolecules are deposited on substrate and passivate the gold electrode. According to literatures, the oxidation of most thiophene derivatives in acidic aqueous solution begins at about 0.95 V [16,24,25,40]. If the potential is shifted to more positive region, the over-oxidation of monomers would occur.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, for monomer modified Au(1 1 1) electrodes, the characteristic peaks of Au(1 1 1) disappear and double layer charging zone prevails from 0 to 0.9 V. This indicates that admolecules are deposited on substrate and passivate the gold electrode. According to literatures, the oxidation of most thiophene derivatives in acidic aqueous solution begins at about 0.95 V [16,24,25,40]. If the potential is shifted to more positive region, the over-oxidation of monomers would occur.…”
Section: Methodsmentioning
confidence: 99%
“…The flat-lying and vertical orientation could be controlled by potential. However, EDOT molecules only take flat-lying orientation in all ordered adlayers in the double layer region [24]. It is proposed that the bigger p-conjugated component is benefit for enhancing molecule-substrate interaction to make molecules flatly adsorb on the electrode surface.…”
Section: Bdd Adlayermentioning
confidence: 99%
See 1 more Smart Citation
“…27 It was found that both ordered and disordered domains coexisted in the EDOT adlayer, which were characterized by vacancy islands with the subsequent lifting of the reconstruction lines upon adsorption of the EDOT molecules. Electrochemical polymerization by shifting the potential positively resulted in the formation of pEDOT clusters rather than the single chain wires.…”
Section: Electrochemistry-induced 2d Polymerizationmentioning
confidence: 99%
“…A number of scanning tunneling microscopy (STM) studies have been devoted to thiophenes, oligothiophenes, and polythiophenes adsorbed onto highly oriented pyrolytic graphite (HOPG) (Rossi et al, 1998; Azumi et al, 2000; Mena-Osteritz et al, 2000; Mena-Osteritz, 2002; Brun et al, 2004; Abdel-Mottaleb et al, 2006; Yang et al, 2007; Zhang et al, 2009), molybdenum disulfide (MoS 2 ) (Azumi et al, 1999), and Au(111) (Glowatzki et al, 2007; Kiel et al, 2007; Tongol et al, 2009, 2010; Lapitan et al, 2010; Wang et al, 2010) surfaces. Frequently, these STM results showed that oligothiophenes with alkyl substituents at β-positions tended to form ordered structure with the alkyl side chains aligned along one of the main crystallographic axes of the substrate on HOPG (Azumi et al, 2000; Mena-Osteritz, 2002; Abdel-Mottaleb et al, 2006; Yang et al, 2007; Zhang et al, 2009) and Au(111) (Tongol et al, 2009, 2010; Lapitan et al, 2010; Wang et al, 2010) surface. Regioregular polythiophenes always form self-organized polycrystals in comparable lamellar structures with threefold symmetry on HOPG (Mena-Osteritz et al, 2000; Brun et al, 2004) surface both at the liquid-solid interface and in dry films.…”
Section: Introductionmentioning
confidence: 99%